KNOWLEDGE, PERCEPTION AND ATTITUDE OF BALINESE COMMUNITY TOWARD GENDER CONCEPT AND GENDER EQUITY AND EQUALITY - Arjani, Ni Luh; Wiasti, Ni Made; Sudantra, I Ketut (PIRAMIDA, 2012)
Gender inequity and inequality in the community would restrict developmentprocess. Therefore, struggle toward gender equity and equality is become interestingglobal issue for the world and also Indonesia and Bali.The aims of this study is 1) to analyze knowledge, perception, and attitude ofBalinese community toward gender concept and gender equity and equality, and 2) toknow implementation of gender role in the family and community. This study is carriedout in the three regencies/city in Bali, i.e. Buleleng, Tabanan and Denpasar. In eachregency/city, two types of village is determined that are urban and rural. Data arecollected by implementing structured interview based on questionnaire which is asked to120 respondents and completed with in-depth interview based on interview guidance tosome key respondents.The finding shows that most of respondent (68.30 %) have not known genderconcept, means that only 21.70 percent stated that they already known it, and they havedifferent understanding both about gender term and gender equity and equality. Withregard to gender equity and equality, only 24.20 percent of respondent report that theyhave read and heard about this term. However, when it is related to gender equity andequality program, most of them (91.60 %) of respondent stated that they agree with sucha program. In addition, it is also found that in the reality, almost all respondent actuallyhave implemented job sharing between man and women flexibly, means that they swapthe role of each other depend on situation and condition. This reality reflects that there isa shifting of thinking pattern of the community from rigid toward flexible division of job.Based on the findings, it can be concluded that although only small number ofcommunity member have known and understand gender concept and gender equity andequality, actually they have implemented it in their daily life. In general, communitymember also agree for changing their attitude toward gender role, so the condition ofgender equity and equality can be achieved.
Keywords: gender, gender equity and equality